2014
DOI: 10.1016/j.bmcl.2013.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and tyrosinase inhibitory activity of rhododendrol glycosides

Abstract: The concise synthesis of rhododendrol glycosides 3-8, which are novel derivatives of (+)-epirhododendrin (1) and (-)-rhododendrin (2), has been achieved in six steps from benzaldehyde 9. The key reactions include aldol condensation and trichloroacetimidate glycosylation. From biological studies, it has been determined that synthetic derivatives of 1 and 2 possess potent tyrosinase inhibitory activity. Particularly, the inhibitory activity of cellobioside 8 (IC50=1.51μM) is six times higher than that of kojic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 38 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…When only 1 equiv of 16 was used in this step, an acetylated derivative of 16 was detected as a major product. 23 The b facial attack of acceptor 16 was probably blocked because the oxocarbenium intermediate generated from 25 was sterically hindered. 36 Although several alternative modifications, such as a change of Lewis acid and the application of Koenigs-Knorr conditions were explored, the glycosylation could not be further optimized.…”
Section: Synthesis and Tyrosinase Inhibitory Activities Of 7-12mentioning
confidence: 99%
See 2 more Smart Citations
“…When only 1 equiv of 16 was used in this step, an acetylated derivative of 16 was detected as a major product. 23 The b facial attack of acceptor 16 was probably blocked because the oxocarbenium intermediate generated from 25 was sterically hindered. 36 Although several alternative modifications, such as a change of Lewis acid and the application of Koenigs-Knorr conditions were explored, the glycosylation could not be further optimized.…”
Section: Synthesis and Tyrosinase Inhibitory Activities Of 7-12mentioning
confidence: 99%
“…33 IC 50 of the mixture of 1 and 2 could not be estimated within 100 lM. 23 Accordingly, tyrosinase inhibitory activity was significantly improved by the introduction of a hydroxy group at C-2 0 . In particular, the activity of 4 containing the R-stereogenic center at C-2 was two-fold higher than that of 3.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There have been several reports on the biologically active glycosides. [36][37][38] Both quercetin 3-␤-glucoside and quercetin 4 -␤glucoside have been reported to show inhibitory action on cancer cell proliferation. 36 Iwadate et al…”
Section: Antioxidant Antiallergic Antiphosphodiesterase Activities mentioning
confidence: 99%
“…reported that two epimers of rhododendrol 2-␤-glucoside exerted efficient tyrosinase inhibitory activity stronger than kojic acid, and that the Repimer had higher activity than the S-epimer. 37 It has been reported that the N-acetylglucosamine analog of oleanolic acid showed high anticancer activity, which was about three times stronger than that of the aglycone (i.e., oleanolic acid). 38 To clarify the efficiency of glycosylation for the physiological and pharmacological activities of stilbenes, we examined several in vitro bioassays of stilbenes and their glycosides.…”
Section: Antioxidant Antiallergic Antiphosphodiesterase Activities mentioning
confidence: 99%